2015
DOI: 10.1080/13573322.2015.1114917
|View full text |Cite
|
Sign up to set email alerts
|

Developing children: developmental discourses underpinning physical education at three Scottish preschool settings

Abstract: This paper reports on one aspect of a study that investigated the place and meaning of 'physical education' to practitioners and children at three preschool settings in Scotland. We employed a poststructural type of discourse analysis to examine the developmental discourses the 14 participating practitioners drew on when talking about 'physical education' at preschools, during semi-structured interviews. Three main discourses around the notion of developmentalism were identified during analysis of the adults' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…how the participants justified their views), and looked for gaps, resistances and counter-discourses, in order to determine the effects of the discourses (Carabine, 2001). Following the approach of McEvilly et al (2017) and Tynan and McEvilly (2017), I probed around the following analytical questions: what discourses related to PE are circulating? What 'truths' and meanings about PE do the participants construct and privilege?…”
Section: Methodsmentioning
confidence: 99%
“…how the participants justified their views), and looked for gaps, resistances and counter-discourses, in order to determine the effects of the discourses (Carabine, 2001). Following the approach of McEvilly et al (2017) and Tynan and McEvilly (2017), I probed around the following analytical questions: what discourses related to PE are circulating? What 'truths' and meanings about PE do the participants construct and privilege?…”
Section: Methodsmentioning
confidence: 99%
“…This is because research suggests that major changes take place in all domains of childhood development in the preschool years (Ross, 2013). The development of a child is a holistic process, in which motor, cognitive, and social skills are of particular importance as children learn through movement (McEvilly et al, 2017). PE in preschool settings is critical for providing children opportunities to develop their skills in all domains through participation in movement activities (Martínez-Bello et al, 2021; Ross, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…PE in preschool settings is critical for providing children opportunities to develop their skills in all domains through participation in movement activities (Martínez-Bello et al, 2021; Ross, 2013). This can occur by developing skills, knowledge, and attitudes to promote active lifestyles (Kirk, 2005; McEvilly et al, 2017). Despite this importance, the low quality of PE in the preschool years has constantly been challenging across the world (McEvilly et al, 2013; Tsangaridou, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There has been increasing worldwide attention on the educators’ quality and effectiveness in the professional literature (Han and Neuharth-Pritchett, 2010; Hmelak and Lepicnik Vodopivec, 2015; Kyriakides et al, 2017; Strong, 2011; Wen et al, 2011; Wilcox-Herzog, 2002), as well as on educators’ beliefs about PE in ECEC (Hastie et al, 2016; McEvilly et al, 2015; Stirrup, 2016; Tsangaridou and Genethliou, 2014). McEvilly et al (2017) suggested that it is important to continue investigating the discourses concerning PE in ECEC among practitioners, policy-makers and researchers.…”
Section: Introductionmentioning
confidence: 99%